2017
DOI: 10.1177/1934578x1701200723
|View full text |Cite
|
Sign up to set email alerts
|

A New Stilbene from the Root of Cassia sieberiana D.C. (Fabaceae)

Abstract: A new stilbene (1) was isolated from the root of Cassia sieberiana D. C. together with thirteen known compounds, one stilbene (2), three flavonoids (3–5), six anthraquinones (6–11), two triterpenes (12–13), and phytosterol (14). Their structures were identified using spectroscopic techniques and by comparison of the spectral data with those previously reported in the literature. Compounds 10 – 13 were isolated from C. sieberiana for the first time. Compounds 1, 2 and 3 exhibited significant inhibitory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…According to the available literature, phenolic compounds or their derivatives were reported to exhibit antioxidant activities [ 27 ]. Researchers demonstrated that chrysophanol has no activity against DPPH and ABTS + radicals [ 28 ]. However, other researchers showed that the compound had a scavenging effect on DPPH radical (IC 50 value of 26.56 μ g/mL).…”
Section: Resultsmentioning
confidence: 99%
“…According to the available literature, phenolic compounds or their derivatives were reported to exhibit antioxidant activities [ 27 ]. Researchers demonstrated that chrysophanol has no activity against DPPH and ABTS + radicals [ 28 ]. However, other researchers showed that the compound had a scavenging effect on DPPH radical (IC 50 value of 26.56 μ g/mL).…”
Section: Resultsmentioning
confidence: 99%
“…263,264 The results on its hydrogenated derivative, 2,3-dihydroamentoflavone (165), also suggest a similar pattern. 263 In a study by Ho et al, 252 the inhibitory activity of procyanidin C1 (173), procyanidin B2 (174), and procyanidin B5 (175) were also reported. In this study, all these three oligomeric flavonoids outperformed acarbose in the both two α-glucosidase and α-amylase inhibition assay, with the IC50 values varied below 10 µM.…”
Section: Isoflavonoidmentioning
confidence: 95%
“…263,264 The results on 2,3-dihydroamentoflavone (165) also suggest a similar pattern. 263 In a study by Ho et al, 251 the inhibitory activity of procyanidin C1 (173), procyanidin B2 (174), and procyanidin B5 (175) were also reported. In this study, all these three oligomeric flavonoids outperformed acarbose in the both two α-glucosidase and α-amylase inhibition assay, with the IC50 values varied below 10 µM.…”
Section: Oligomeric Flavonoidsmentioning
confidence: 97%